Modified steel basket technique for the treatment of equine cervical vertebral stenotic myelopathy - a case report - Frederico Fernandes Araújo; Monalisa Lukascek Castro; Luciane Laskoski; Mariana Pavelski; Ivan Deconto; Peterson Triches Dornbusch (Semina: Ciências Agrárias, 2015)
Cervical vertebral stenotic myelopathy (CVSM), also known as cervical ataxia or wobbler syndrome, is caused by the narrowing of the medullary canal due to a malformation of the cervical vertebrae, resulting in compression of the spinal cord and neurological alterations such as ataxia, hypermetria, weakness, and abnormal stance. The treatment options can be conservative or surgical, with varied effectiveness. The most appropriate surgical technique in the majority of cases is arthrodesis, providing quick and efficient decompression of the spinal cord. The goal of this case report is to present an equine patient with CVSM that was surgically treated using a new modified cage model. The diagnosis was based on history, clinical signs and radiographic evidence of spinal cord compression between the C3 and C4 vertebrae, after ruling out possible infectious agents. The surgical procedure for the decompression and stabilization of the point of stenosis was performed using a modified Cloward’s technique and a new cage model fixed with two screws. Evidence of fusion was obtained by periodic radiographs over six months of postoperative care. The new cage model used in this surgery proved to be efficient for the decompression and stabilization of the vertebrae, allowing arthrodesis development and remission of the clinical signs. Fixation of the cage with screws reduces the risk of migration of the implant.